LO33: Sharing and teaching electrocardiograms to minimize infarction. (May 2020) - McLaren, J.; Taher, A.; Chartier, L.
Abstract : Background: Every 30-minute delay to ST-Elevation Myocardial Infarction (STEMI) reperfusion increases one-year mortality by 7.5%. A local audit found that the third of patient electrocardiograms (ECGs) not initially meeting classic STEMI criteria had an ECG-to-Activation (ETA) time of over 90 minutes, more than five times that of classic STEMIs. However, three quarters of "STEMI negative" ECGs met STEMI-equivalent patterns or rules for subtle occlusion, uncovering an opportunity for improvement. Aim Statement: We aimed to reduce ETA time, from initial emergency department (ED) ECG to activation of the cath lab, for patients whose ECGs did not meet classic STEMI criteria, by 30 minutes within one year (i.e. by Dec 2019). Measures & Design : We reviewed all ED Code STEMIs over a 35-month pre-intervention period. Root Cause analyses, including Ishikawa diagram and Pareto chart, led to our Plan-Do-Study-Act cycles: 1) a survey to engage our team; 2) a Grand Rounds presentation as an educational strategy; and 3) weekly web-based feedback to all ED physicians on STEMI-equivalents and subtle occlusions, using recent local cases. Our outcome measures were ETA times, stratified by ECGs not initially meeting STEMI criteria (primary) and those that did (secondary). Our process measures were the number of website visits and page views. Our balancing measure was the proportion of Code STEMIs without culprit lesion. We used Statistical Process Control (SPC) charts with usual special cause variation rules. Evaluation/Results : ETA time for the 37.5% of 56 ECGs that did not meet classic STEMI criteria decreased from 97.5 to 53.7 minutes (min), a 43.8-min absolute decrease (p = 0.037), while those meeting STEMI criteria remained the same (16.5 to 18.2min, p = 0.75). SPC charts did not show special cause variation. There were 2, 634 page views (65.9/week) and 1, 092 visits (27.3/week), in a group of 80 physicians—i.e. a third of the group each week. There was no change in Code STEMIs without culprit lesions (28.0 % to 23.3%, p = 0.41). Discussion/Impact : We reduced ETA time by 43.8min for the one third of patients with culprit lesions not initially meeting classic STEMI criteria, a magnitude associated with mortality impact. To do so, we used a multi-modal educational strategy including a novel web-based feedback approach to all ED physicians. Local feedback and education on this challenging-to-diagnose subgroup, guided by ETA time as a quality metric, could be replicated in other centres.